2017
DOI: 10.1007/s00347-017-0590-z
|View full text |Cite
|
Sign up to set email alerts
|

Laserassistierte Blepharoplastik

Abstract: Blepharoplasty is one of the most frequently performed plastic cosmetic interventions. For this purpose the CO laser is an instrument that can be used as a laser scalpel to cut as well as in its ablative function to remove skin irregularities, such as scars and tumors and also to treat changes of the skin due to aging. Fractionated laser irradiation reduces the duration of skin redness and the postoperative rehabilitation time after a resurfacing. The advantages of the CO laser are a gentle intraoperative prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Benefits of using the CO 2 laser are reduced operative time, less bleeding, superior intraoperative visibility, less bruising and swelling, no pain, and a shorter recuperation period. [19][20][21] It is also possible that the laser can have a more potent effect on corneal tissue than scalpels. The heat generated by the cautery and the ablative effects of the CO 2 laser may account for the stromal tissue loss and slow closure of the epithelial defects seen in these cases that would not have been seen with a scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of using the CO 2 laser are reduced operative time, less bleeding, superior intraoperative visibility, less bruising and swelling, no pain, and a shorter recuperation period. [19][20][21] It is also possible that the laser can have a more potent effect on corneal tissue than scalpels. The heat generated by the cautery and the ablative effects of the CO 2 laser may account for the stromal tissue loss and slow closure of the epithelial defects seen in these cases that would not have been seen with a scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, however, underlined the disadvantages of using the CO 2 laser compared with the steel scalpel attributing it to its cost in terms of purchasing and maintaining the laser equipment, the need for additional and extensive laser training for surgeons and assistants, and the need for two assistants rather than the one needed for scalpel surgery. 45 However, the CO 2 laser leads to a number of advantages in comparison to theses surgical approaches, already discussed above, such as gentle intraoperative preparation and less postoperative swelling due to an additional cauterization of blood vessels 46 and the possibility to perform precise incision and hemostasis with the same device 47 Moreover, the possibility of using fractionated CO 2 and 1540-nm laser in the lower periorbital area allows us to achieve a greater shrinkage effect than using fractionated CO 2 alone. 20 Collagen production and remodeling continues for several months after blepharoplasty CO 2 laser treatment as reported in literature 48 In addition, a study using cytotoxicity and proliferation analysis and confocal analysis showed that the 1540-nm laser leads to cell proliferation and a significant increase in type III collagen compared to a nonirradiated control sample and therefore guarantees skin rejuvenation of the lower periorbital area.…”
Section: Discussionmentioning
confidence: 99%